Inbound traffic engineering for multihomed ASs using AS path prepending. - Chang, R.K.C (IEEE Network : the magazine of global information exchange)
This article considers the AS path prepending approach to engineer inbound traffic for multihomed ASs. The AS path prepending approach artificially inflates the length of the AS path attribute on one of the links in hopes of diverting some of the traffic to other links. Unlike the current practice that determines the prepending length in a trial-and-error way, we propose AutoPrepend, a systematic and automated procedure for conducting prepending. The entire process consists of four components: passive measurement, active measurement, traffic change prediction, and AS path update. The main idea is to predict the traffic change due to a new prepending value before effecting the change. We have also employed a number of mechanisms to minimize intrusion into the normal operation of the Internet. We have deployed AutoPrepend on a noncommercial site and evaluated its effectiveness based on the measurements collected over six months.